Evaluación de la gestión administrativa para la mejora de la calidad del servicio que brinda el Centro de Salud Tipo C Chone - Balderramo Lélez, Shirley Gabriela (2020)
With the aim of evaluating the administrative management of the Type C Chone Health Center to improve the quality of the service, by using the deductive method, an investigation was carried out based on scientific and legal theories that supported the research, they were delimited each of the activities that influenced such as: identifying the entity's administrative management processes, where it was possible to analyze that the institutional POA designs goals towards compliance with the unit's operational processes and that there is positive coverage to address the demand, however, there are problems in the supply of medicines, materials and instruments. Subsequently, by means of the inductive method, investigation techniques were used as an interview with the Director in charge in order to evaluate the administrative management, determining that the assigned budget does not allow to cover the needs and procedures established in the POA, so there is a deficient payment of inputs to fulfill the established objectives; in sequence, through the management indicators, an overuse of human resources was diagnosed due to the fact that the number of patients scheduled for the day was not met; Likewise, a non-compliance is observed in the procedures focused on improving the performance of human resources through training. Finally, with the results obtained, the proposal for improvement actions was considered, where new strategies are considered that will help improve the effectiveness and efficiency of administrative management.